An Evaluation of the Effects of Varying Magnitudes of Reinforcement on Variable Responding Exhibited by Individuals With Autism. Issue 6 (November 2019) - Ferguson, Raechal H.; Falcomata, Terry S.; Ramirez-Cristoforo, Andrea; Vargas Londono, Fabiola
Interventions aimed at increasing communicative response variability hold particular importance for individuals with autism spectrum disorders (ASD). Several procedures have been demonstrated in the applied and translational literature to increase response variability. However, little is known about the relationship between reinforcer magnitude and response variability. In the basic literature, Doughty, Giorno, and Miller evaluated the effects of reinforcer magnitude on behavioral variability by manipulating reinforcer magnitude across alternating relative frequency threshold contingencies, with results suggesting that larger reinforcers induced repetitive responding. The purpose of this study was to translate Doughty et al.'s findings to evaluate the relative effects of different magnitudes of reinforcement on communicative response variability in children with ASD. A Lag 1 schedule of reinforcement was in place during each condition within an alternating treatments design. Magnitudes of reinforcement contingent on variable communicative responding were manipulated across the two conditions. Inconsistent with basic findings, the results showed higher levels of variable communicative responding associated with the larger magnitude of reinforcement. These outcomes may have potential implications for interventions aimed at increasing response variability in individuals with ASD, as well as future research in this area.